2019
DOI: 10.1002/chem.201904344
|View full text |Cite
|
Sign up to set email alerts
|

Iron Coordination to Hollow Microporous Metal‐Free Disalphen Networks: Heterogeneous Iron Catalysts for CO2 Fixation to Cyclic Carbonates

Abstract: This work shows that ah ollow and microporous metal-free N,N'-phenylenebis(salicylideneimine) (salphen) network (H-MSN) can be engineered by Sonogashira coupling of [tetraiodo{di(Zn-salphen)}] building blocks with 1,4-diethynylbenzene in the presence of silica templates and by successive Zn and silica etching. Iron(III) ions could be incorporatedi nto the H-MSN to form hollow and microporous Fe-disalphen networks (H-MFeSN) with enhanced microporosity and surface area. TheH -MFeSN showede fficient catalytic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Recently, MOP-based Lewis acid catalysts have been applied to the CO 2 fixation to cyclic carbonates. However, the studies at ambient temperature and under 1 atm CO 2 pressure are relatively rare. As a representative example, Xie et al reported cyclic carbonate yields of 51.6% and 81.5% from styrene oxide (SO) and propylene oxide, respectively, through catalytic reactions of MOPs bearing 0.44 mol % Cr-salen and 0.488 mol % Co-salen for 48 h at ambient temperature and pressure. , Given this information, we tested 0.50 mol % ZnP-MOPs for the CO 2 fixation with SO to cyclic carbonate , at ambient temperature (40 °C) under 1 atm (Figure d). The order of catalytic performance was ribbon-like ZnP-MOP-4 ≫ tubular ZnP-MOP-6 > granular ZnP-MOP-1 with cyclic carbonate yields of 95 ± 3%, 53 ± 5%, and 32 ± 2%, respectively, after 48 h (Figure d).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, MOP-based Lewis acid catalysts have been applied to the CO 2 fixation to cyclic carbonates. However, the studies at ambient temperature and under 1 atm CO 2 pressure are relatively rare. As a representative example, Xie et al reported cyclic carbonate yields of 51.6% and 81.5% from styrene oxide (SO) and propylene oxide, respectively, through catalytic reactions of MOPs bearing 0.44 mol % Cr-salen and 0.488 mol % Co-salen for 48 h at ambient temperature and pressure. , Given this information, we tested 0.50 mol % ZnP-MOPs for the CO 2 fixation with SO to cyclic carbonate , at ambient temperature (40 °C) under 1 atm (Figure d). The order of catalytic performance was ribbon-like ZnP-MOP-4 ≫ tubular ZnP-MOP-6 > granular ZnP-MOP-1 with cyclic carbonate yields of 95 ± 3%, 53 ± 5%, and 32 ± 2%, respectively, after 48 h (Figure d).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In terms of a synthetic strategy, tailored functionality can be incorporated into MOPs by a predesigned building block approach and a postsynthetic modification method. For example, through the predesigned building block approach, building blocks with emissive moieties can be designed and prepared . Tetraphenylethylene moieties are known to exhibit aggregation-induced emission (AIE) through the restriction of intramolecular motion .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] However, most of these systems often need solvents or homogeneous additives, high pressures and temperatures. Recently, considerable effort has been devoted to the development of efficient catalytic systems for the synthesis of cyclic carbonates such as nano-PDA/KI, [11] ZnI2/NEt3, [12] (Cp2TiCl2)/KI, [13] ZnCl2/Al2O3-TBAI, [14] Zn-SBA-15/KI, [15] metal complexes, [16][17][18][19] organocatalysts, [20][21][22] MOFs, [23][24][25] MgO/TBAB/Bu4NBr, [26] Bp-Zn@MA, [27] H-MFeSN, [28] and others. [29][30][31] In spite of their potential utility, however, most of them still have problems such as harsh reaction conditions, use of expensive reagents, cumbersome product isolation and catalyst reusability procedures.…”
Section: Introductionmentioning
confidence: 99%